Pengaruh Model Pembelajaran Berdiferensiasi Terhadap Keterampilan Berpikir Kritis Peserta Didik Pada Mata Pelajaran Matematika Kelas IV Di MIN 4 OKU Timur - Laila Kartika Rahayu; Ida Fiteriani; Hasan Sastra Negara (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Critical thinking skills are one of the essential competencies that students need to develop in mathematics learning. However, based on preliminary observations conducted at MIN 4 OKU Timur, students' critical thinking skills were still relatively low due to their limited involvement in the learning process. This study aimed to determine the effect of the differentiated learning model on the critical thinking skills of fourth-grade students in mathematics at MIN 4 OKU Timur. The study employed a quantitative approach with a quasi-experimental method using a Posttest-Only Control Design. The sample consisted of 49 students, including 26 students in the experimental class and 23 students in the control class. Data were collected through essay tests designed to measure students' critical thinking skills. The data were analyzed using normality tests, homogeneity tests, and hypothesis testing through the Independent Samples t-Test. The results showed that the average posttest score of the experimental class was 71.08, which was higher than that of the control class, namely 60.48. Furthermore, the hypothesis test yielded a significance value of 0.013, which was lower than 0.05. Therefore, it can be concluded that the differentiated learning model has a significant effect on students' critical thinking skills in mathematics learning among fourth-grade students at MIN 4 OKU Timur.